Estimation of shock degrees of eucrites using X-ray diffraction and petrographic methods - Kanemaru, Rei; Imae, Naoya; Yamaguchi, Akira; Takenouchi, Atsushi; Nishido, Hirotsugu (Polar Science, 2020)
We examined the shock effects on 12 basaltic and 4 cumulate eucrites, using the petrographic and X-ray diffraction (XRD) methods. Petrographic and XRD measurements were conducted on the same polished sections of the eucrites. On the basis the ranges of undulatory extinction angles and occurrence of maskelynite, we defined five shock degrees: A (unshocked to very weakly shocked), B (weakly shocked), C (moderately shocked), D (moderately to highly shocked), and E (highly shocked). We performed macroscopic XRD analyses of the polished sections of the eucrites using the in-plane rotation method. The results of XRD analysis are correlated with the shock degrees obtained through the petrographic observations. The averaged full width at half maximum (FWHM) values of diffraction peaks are increase from shock degree A to E. As the FWHM value reflects the lattice spacing, the observed increase in the averaged FWHM values indicates the reduction in their crystallinities because of shock metamorphism. Therefore, the petrographic and XRD methods are both useful indicators in the evaluation of the shock degrees of eucrites. journal article